Performance, combustion and emissions analysis of water emulsified biodiesel in a diesel engine - Wan Nor Maawa, Wan Ghazali (2020)
Biodiesel is fast becoming a major role in lessening the dependency on petroleum fuel. Biodiesel is considered as promising fuel with properties that will allow low percentage biodiesel-diesel fuel blends to operate smoothly in a conventional compression ignition engine without modifications. Currently, the biodiesel mandate for Malaysia stands at 7% and is likely to rise to 10%. The use of biodiesel in diesel engines reduces certain greenhouse gas emissions considerably, but NOx production remains high compared to diesel. The objectives of this study are to characterize the physicochemical properties of blended fuel B20 and effect of water in terms of emulsion, to analyze the combustion characteristics of blended fuel B20 emulsified with different percentages of water to evaluate the performance and exhaust emissions of fuel B20 emulsified with water in diesel engine. The emulsion fuels were prepared using external force. The stability period for the emulsion fuels were observed in terms of days and the droplet particle measurement was carried out using inverted metallurgical microscope connected to a computer. The experimental characterization of the blended fuel and emulsion fuel properties such as kinematic viscosity, density and calorific value was conducted according to standard ASTM D7467 and compared with diesel fuel. Experimental works were carried out on a multi-cylinder, direct injection diesel engine to investigate the combustion characteristics, engine performance and exhaust emission parameters. The days of stability of the emulsion is decreased when the water proportion is increased. On the contrary, the mean particle size of the droplet increased when water content increased. The fuel properties results showed that the kinematic viscosity and density for all emulsion fuels reduced compared to diesel fuel. The reduction increased as the water percentage increased. On the other hand, compared to conventional diesel, there was significant reduction in all emulsion fuel calorific values except the emulsified blend with 5% of water. The calorific value for emulsion fuel with 5% of water showed comparable results with the base fuel. At same operating conditions, the in-cylinder pressure traces for blended fuel and emulsified blended fuels are comparable to the conventional diesel. However, at all loads, the emulsion fuel with 5% water proportion showed significant reduction in peak in-cylinder pressure and maximum rate of heat release compared to diesel and blend fuel. The engine torque for low water content showed some improvements compared to diesel and biodiesel-diesel blend. Similarly, the brake power for emulsion fuel with 5% of water increased significantly at low loads and comparable at high loads. All the emulsion fuels exhibited better thermal efficiency compared to diesel fuel at all operating conditions except for emulsion fuel with 30% of water during 40% load. The formation of NOx emissions was reduced significantly with increase of water proportions at all operating conditions. The highest reduction obtained by emulsion fuel with 30% of water at 40% engine load. On the other hand, the HC and CO2 emissions for emulsion fuels increased compared to conventional diesel. In conclusion, the emulsification of blend biodiesel-diesel fuel is a proven method to reduce the formation of NOx emissions. Overall, these findings have contributed to the fundamental understanding of water emulsification with POME biodiesel-diesel blend operated with diesel engine.